Diurnal variation of specific tests` performance and related psychological aspects in young judo athletes - Ouergui, I.; Delleli, S.; Chtourou, H.; Selmi, O.; Bouassida, A.; Bouhlel, E.; Franchi, E. (Research Quarterly for Exercise and Sport, 2023)
Purpose This study investigated the effects of time-of-day on judo athletes` performances and the associated psychological variables and perceived exertion following judo-specific tests.